(3af GdJQLeI GdEYdGejI aj hSGFd GdGJUGd GdLeGgjQj (B/s - (3TcQj, YHO GdeLjOs ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ,s, 2004)
(3TQM cGed dCUhd hbhGYO GdJQLeI GdEYdGejI TQM cGed dbhGYO GddZI GdEfLdjRjI GdhXjajI (B- (3JOQjHGJ h JWHjSbGJ TGedI Ydi GdJQLeI GdEYdGejI (B- (3JYHjQGJ h eUWdMGJ EYdGejIs
Keywords: (3GdGJUGds; (3hSGFd GdGJUGds; (3hSGFd GdGJUGd GdLeGgjQjs; (3GdEYdGes